INFLUENCE OF CENTRALIZED OPERATION CONTROLS ON THE PERFORMANCE OF PUBLIC SERVICE VEHICLE FIRMS OFFERING LONG DISTANCE NIGHT TIME PASSENGER SERVICES IN KENYA - Mbao, Mbao Jacob Nyaa; Mwangangi, Dr. Patrick (European Journal of Business and Strategic Management, 2017)
Purpose: The study aimed at establishing the influence of centralized operation controls on the performance of PSV firms offering Night time long distance passenger services in Kenya. Materials and methods: This study targeted the SACCOs or Companies that have complied and have been issued with Road Transport Licences to operate Night Time Long Distance Passenger Services. Because of the specific character of these organizations the sample was selected by the purposive sampling method, the sampling frame being the records in the NTSA data bank, where only 39 firms are listed for this class of licences. This study adopted a descriptive research design and due to the fact that the population is very small, a census was undertaken. A questionnaire having both open and closed ended questions for primary data collection was used while the secondary data was obtained from documentary sources explaining theoretical and empirical information on diversity of influencing factors on PSV Industry performance. The data was collated, computerized and analyzed using SPSS Version 24. This software analyzed the data into percentages, means and standard deviations and using quantitative techniques the findings were presented in form of frequency distribution tables and pie charts. Results: The study found out that use of Centralized Operations Control influences performance of the PSV industry as it influences in pooling of professional staff, effective and efficient fleet communication, the reduction of transaction costs, quicker and integrated data collection and analysis, it was also established that it also influences flexible route planning and management. Recommendations: The study recommends all the companies operating public service vehicles should have centralized operations to reduce transaction cost. This will facilitate in pooling of professional staff who in turn improve the services offered.